Blood meal survey reveals insights into mosquito-borne diseases on the island of Santiago, Cape Verde - Gonçalves, Adéritow Augusto Lopes Macedo; Dias, Adelina Helena Campinha; Monteiro, Davidson Daniel Sousa; Varela, Isaías Baptista Fernandes; da Veiga Leal, Silvânia (Frontiers in Tropical Diseases, 2023)
Transmission of pathogens by blood-sucking insects to humans and other animals depends on vector-host interactions. Yet unexplored in Cabo Verde, mosquito feeding behavior plays a crucial role in pathogen transmission. Herein, we aimed to explore through blood meal analysis the relationship between mosquito species and common hosts in the Santiago Island, Cabo Verde. Engorged female mosquitoes were collected by mechanical aspirations from May 2016 to December 2017 in three municipalities of Santiago Island (Praia, Santa Cruz, and Santa Catarina). Blood feeding behavior for each municipality was assessed through blood meal analysis using Enzyme-Linked Immunosorbent Assay (ELISA). We were able to determine that single-host blood meals were common in Aedes aegypti, Anopheles arabiensis, and Culex pipiens s.l.. In gen-eral, the mosquitoes preferred to feed on humans, dogs, and chickens and multiple-host, mainly two hosts. Human Blood Index (HBI) was highest (1.00) in Ae. aegypti with the lowest (0.40) observed in An. ara-biensis. Among single-host blood meals significant high likelihood of Cx. pipiens s.l. and low likelihood of An. arabiensis to feed on humans were observed (respectively, LOR = 0.85; LOR = -2.44). Also, high likeli-hood of Ae. aegypti to feed on humans was observed but this was not statistically significant (LOR = 0.85). Overall, our findings demonstrated a lack of feedings preference in Culex pipiens s.l., compared to Ae. ae-gypti and An. arabiensis. These results provide insights on possible parasites transmission and pathogens spillover/spillback, which threaten human/animal health and the economy in Cabo Verde.